Potential epigenetic molecular regulatory networks in ocular neovascularization - Hu, Qiang; Zhang, Xue; Sun, Minghao; jiang, Bo; Zhang, Zhongyu; Sun, Dawei (Frontiers in Genetics, 2022)
Neovascularization is one of the many manifestations of ocular diseases, including corneal injury and vascular diseases of the retina and choroid. Although anti-VEGF drugs have been used to effectively treat neovascularization, long-term use of anti-angiogenic factors can cause a variety of neurological and developmental side effects. As a result, better drugs to treat ocular neovascularization are urgently required. There is mounting evidence that epigenetic regulation is important in ocular neovascularization. DNA methylation and histone modification, non-coding RNA, and mRNA modification are all examples of epigenetic mechanisms. In order to shed new light on epigenetic therapeutics in ocular neovascularization, this review focuses on recent advances in the epigenetic control of ocular neovascularization as well as discusses these new mechanisms.